Properties of concrete containing palm oil fuel ash (POFA) as partial sand replacement - Rathey, Paramasivam (2017)
As the second largest global palm oil producer, Malaysia has the massive daily wastage. Palm oil fuel ash (POFA) is commonly found as agricultural waste that is uncontrollably dumped in landfills. An expected 10MT/year total POFA waste is produced in Malaysia alone and this amount rises every year. Besides, extensive mining of natural river sand in large amount to meet the increasing demand of concrete production for the use in rapidly developing construction industry has posed the risk of natural aggregate depletion and ecological imbalance in future. The motive of this kresearch is to reduce the river sand mining and environmental pollution caused by POFA by partially replacing the POFA with sand in concrete. The objectives of this study is to investigate the effect of POFA as partial sand replacement on compressive strength, splitting tensile strength, water absorption and acid resistance of the concrete. For modified mix the concrete contained various percentages of POFA which is 5%, 10%, 15% and 20%. The moulds that were used in this experiment were cube moulds (100 x 100 x 100) mm and cylinder moulds with diameter of 100mm and 200mm in height. The specimens were subjected to water curing for 28, and 60 days for compressive strength test and splitting tensile strength test. For water absorption test, the testing age was 28 days. For acid resistance test, the concrete cubes were water cured for 28 days and then immersed in Hydrochloric acid solution for 1800 hours and reading was taken for every 100 hours. The study efficiently shows that integration of 10% POFA as partial sand replacement is able to produce good quality of concrete in terms of compressive strength and splitting tensile strength. Moreover, concrete containing POFA absorbs more water than plain concrete. Increase the percentage of POFA used in concrete causes the increase in the percentage of water absorbed by the concrete specimens. Lastly, acid resistance of concrete containing 10% of POFA as partial sand replacement is better than the control concrete.